Resolution Enhancement in Surface Plasmon Resonance Sensor Based on Waveguide Coupled Mode by Combining a Bimetallic Approach - Lee, Kyeong-Seok; Son, Ju Myeong; Jeong, Dae-Yong; Lee, Taek Sung; Kim, Won Mok (MDPI, 2010)
In this study, we present and demonstrate a new route to a great enhancement in resolution of surface plasmon resonance sensors. Basically, our approach combines a waveguide coupled plasmonic mode and a kind of Au/Ag bimetallic enhancement concept. Theoretical modeling was carried out by solving Fresnel equations for the multilayer stack of prism/Ag inner-metal layer/dielectric waveguide/Au outer-metal layer. The inner Ag layer couples incident light to a guided wave and makes more fields effectively concentrated on the outer Au surface. A substantial enhancement in resolution was experimentally verified for the model stack using a ZnS-SiO2 waveguide layer.
Keywords: SENSITIVITY; BIOSENSORS